2021
DOI: 10.25136/2409-7144.2021.9.36560
|View full text |Cite
|
Sign up to set email alerts
|

Gender peculiarities of professional identity in medical dynasties

Abstract: Despite the fact that female employees prevail in modern healthcare system, medicine retains gender differentiation in terms of distribution of authority, career trajectories, pay grade, etc. Such gender bias impedes balanced professional development of the medical personnel, affects their work motivation, and commitment to the profession. Medical dynasties are an important link in reproduction of human capital and preservation of the professional ethos of the medical practice. Therefore, this article explores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
0
0
Order By: Relevance
“…Although 63.8 percent of respondents in Moscow and 25.9 percent of respondents in Rostov-on-Don selected "organization, order, discipline in the military" as motivating factors for joining the military, this option was chosen far less frequently for the Moscow respondents and only slightly for Rostov-on-Don responders when they were asked whether it was important for them at the time of the survey. 461 Second, one's commander's personality and ability to maintain good order and discipline also might affect perceptions of military service that could affect retention. A 2017 survey of 972 former servicemen (officers, warrant officers, sergeants, and privates) in Primorskii Krai (Eastern Military District) 462 showed that 8 percent of respondents decided not to renew their contract or terminated it prematurely because of poor treatment by their commander.…”
Section: Good Order and Disciplinementioning
confidence: 99%
“…Although 63.8 percent of respondents in Moscow and 25.9 percent of respondents in Rostov-on-Don selected "organization, order, discipline in the military" as motivating factors for joining the military, this option was chosen far less frequently for the Moscow respondents and only slightly for Rostov-on-Don responders when they were asked whether it was important for them at the time of the survey. 461 Second, one's commander's personality and ability to maintain good order and discipline also might affect perceptions of military service that could affect retention. A 2017 survey of 972 former servicemen (officers, warrant officers, sergeants, and privates) in Primorskii Krai (Eastern Military District) 462 showed that 8 percent of respondents decided not to renew their contract or terminated it prematurely because of poor treatment by their commander.…”
Section: Good Order and Disciplinementioning
confidence: 99%